2019
DOI: 10.1002/smll.201902186
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of Nanoparticle‐Based Aerogels and Xerogels by Inkjet Printing

Abstract: Nanoparticle‐based voluminous 3D networks with low densities are a unique class of materials and are commonly known as aerogels. Due to the high surface‐to‐volume ratio, aerogels and xerogels might be suitable materials for applications in different fields, e.g. photocatalysis, catalysis, or sensing. One major difficulty in the handling of nanoparticle‐based aerogels and xerogels is the defined patterning of these structures on different substrates and surfaces. The automated manufacturing of nanoparticle‐base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 45 publications
2
51
0
Order By: Relevance
“…9,33,34 We have recently demonstrated that IMPS can also be a useful method to gain insights into the charge carrier dynamics in nanoparticle assemblies. 27,28 The IMPS investigations on cryoaerogels, as shown in the present work, revealed that charge carriers are able to move through the NPL network, which leads to a significant enhancement of the photocurrent. To moreover demonstrate the applicability of the cryoaerogel coated photoelectrodes for photoelectrochemical sensing, we finally conducted a proof-of-principle experiment comprising the measurement of the photoresponse to ferricyanide ions.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…9,33,34 We have recently demonstrated that IMPS can also be a useful method to gain insights into the charge carrier dynamics in nanoparticle assemblies. 27,28 The IMPS investigations on cryoaerogels, as shown in the present work, revealed that charge carriers are able to move through the NPL network, which leads to a significant enhancement of the photocurrent. To moreover demonstrate the applicability of the cryoaerogel coated photoelectrodes for photoelectrochemical sensing, we finally conducted a proof-of-principle experiment comprising the measurement of the photoresponse to ferricyanide ions.…”
Section: Introductionsupporting
confidence: 64%
“…The direct particleparticle contacts were observed to facilitate the charge carrier delocalisation and transport within the structures, leading to prolonged fluorescence lifetimes as well as enhanced photoelectrochemical performance. 19,26,27 In this work, we report on the fabrication and photoelectrochemical characterisation of cryoaerogel coated photoelectrodes which can be applied as photolectrochemical sensors. The prepared cryoaerogels are based on quasi-rectangular CdSe nanoplatelets (NPLs) with a thickness of 4 monolayers (MLs), which should show excellent electrochemical properties due to their very high surface-tovolume ratio.…”
Section: Introductionmentioning
confidence: 99%
“…25 Recently, further studies have been undertaken using spectroelectrochemical measurements to understand the unique optical properties of semiconductor nanoparticle gels and suggest their applicability as sensors. 26,27…”
mentioning
confidence: 99%
“…A similar behavior (only positive photocurrents) was previously reported for inkjet‐printed CdSe/CdS nanorod based xerogel films, with the difference, that in the first hours after electrolyte exposure also negative photocurrents at low bias potentials were observed. [ 48,50 ] The occurrence of a photoelectrochemical photocurrent switching (PEPS) point in the LSVs is typical for CdSe/CdS nanorod monolayers, [ 48,51 ] so that in our case the re‐hydration of the xerogel structure seems to proceed much faster than in case of the inkjet‐printed nanorod xerogels. The re‐hydration of the gel structure as well as charge carrier transport across the nanorod network in general was furthermore investigated by means of IMPS.…”
Section: Resultsmentioning
confidence: 83%
“…This observation could be related the to the continuous hydration of the densely packed xerogel structure, which leads to an increase in the contact area between the particles and the electrolyte. [ 48 ] Nearly stable photocurrents of up to 6 µA cm −2 were obtained after 23 h of electrolyte exposure and very low dark currents were recorded throughout all measurements. Furthermore, only positive photocurrents were registered in the whole investigated time and potential range.…”
Section: Resultsmentioning
confidence: 99%